(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: The concept of functional style has an important place in linguistics and studies how language tools are used in the performance of various tasks of speech. This technique refers to a set of special tools that the language has formed to perform a certain social function. Each functional style has its own lexical, grammatical and stylistic features, which correspond to the purpose, audience and context of speech. The functional style is seen in terms of the practical application of language and ensures the effectiveness of language in the performance of communicative tasks.